Structure and function development during evolution of pentameric ligand gated ion channels - Ortells, Marcelo Oscar (2016)
Ligand Gated Ion Channels (LGICs) are receptors widely involved in vertebrate neuronal and non-neuronal signalling as well as muscle activation. Until very recently these receptors, were only known to exist in animal cells and were named the Cys-loop receptor superfamily because they all share this sub-substructure in their amino acid sequences. Nowadays, these receptors are known as "pentameric" LGICs (pLGICs), to differentiate from other LGICs such us tetrameric glutamate or trimeric ATP LGICs. The first phylogenetic analyses of pLGICs have been performed almost 20 years ago, where only eukaryotic members were known. Currently, we have many more sequences from invertebrate species, but most importantly, we know that these receptors are present in a variety of prokaryotic organisms, a fact predicted in those early studies. Equally important, we have information about the tertiary and quaternary structures from prokaryotic to eukaryotic members, which enlightened our evolutionary understanding of these fascinating and functionally important proteins. Surprisingly, the prokaryotic receptors lack the Cys-loop characteristic of eukaryote receptors which once gave the name to the superfamily. This review focuses on the history of the evolutionary processes of these receptors involved in very important physiological functions as well as in many diseases such as tobacco addiction and schizophrenia, to name just a few.